Progress in Propulsion Physics 2016
DOI: 10.1051/eucass/201608183
|View full text |Cite
|
Sign up to set email alerts
|

Contrail formation in the tropopause region caused by emissions from an Ariane 5 rocket

Abstract: Rockets directly inject water vapor and aerosol into the atmosphere, which promotes the formation of ice clouds in ice supersaturated layers of the atmosphere. Enhanced mesospheric cloud occurrence has frequently been detected near 80-kilometer altitude a few days after rocket launches. Here, unique evidence for cirrus formation in the tropopause region caused by ice nucleation in the exhaust plume from an Ariane 5-ECA rocket is presented. Meteorological reanalysis data from the European Centre for Medium-Rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Visible contrails expand backward and sideways with the altitude from 10 km to 15 km, which is consistent with the results of Ref. [11]. The visible contrails are nonpersistent in the domain at the altitude of 10 km and persistent in the domain at the altitude of 15 km, indicating that the lengths of the visible contrails increase with the altitude from 5 km to 15 km and decrease with the altitude from 15 km to 25 km.…”
Section: Contrail Microphysicssupporting
confidence: 91%
See 1 more Smart Citation
“…Visible contrails expand backward and sideways with the altitude from 10 km to 15 km, which is consistent with the results of Ref. [11]. The visible contrails are nonpersistent in the domain at the altitude of 10 km and persistent in the domain at the altitude of 15 km, indicating that the lengths of the visible contrails increase with the altitude from 5 km to 15 km and decrease with the altitude from 15 km to 25 km.…”
Section: Contrail Microphysicssupporting
confidence: 91%
“…A few scholars focus on rocket contrails (shown in Figure 1), and fewer scholars focus on rocket contrail formation. Voigt et al used the Schmidt-Appleman criterion to judge the rocket contrail formation altitude, indicating that the contrails possibly formed only in the upper troposphere/lower stratosphere region [11]. Platov et al investigated the rocket contrail formation in the upper atmosphere by solving the equations of thermal balance and mass balance of condensing particles, who found that the particle radius increase was only more than 7 nm which was much smaller than the increase in the aircraft cases [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A secondary effect of rocket emissions is an increase in cloudiness, especially in the stratosphere and mesosphere, where clouds are uncommon [3]. These high-altitude clouds typically form in polar regions during extremely cold conditions [35]. In otherwise extremely dry air, rocket-emitted water can supply the necessary ice molecules to grow clouds [35].…”
Section: Ice Nucleation and High-altitude Cloud Formationmentioning
confidence: 99%
“…These high-altitude clouds typically form in polar regions during extremely cold conditions [35]. In otherwise extremely dry air, rocket-emitted water can supply the necessary ice molecules to grow clouds [35]. Increases in rocket launches and a shift towards fuels that emit more water vapor (such as methane and hydrogen) could significantly change high-altitude cloudiness.…”
Section: Ice Nucleation and High-altitude Cloud Formationmentioning
confidence: 99%
“…Most commonly, launchers use aluminized solid propellant, known as "propergol", which is composed of about 68 % of ammonium perchlorate (NH 4 ClO 4 ), 18 % aluminum (Al) and 14 % de polybutadiene. After each launch, a large (contrail) cloud resulting from the combustion of propergol during the flight is released over several km 3 into the atmosphere, and combustion compounds deposit into soils and water bodies (Cencetti et al, 2007;Voigt et al, 2016). For the specific case of Ariane 5, this cloud has been estimated to contain 149 Tn of Al 2 O 3 (resulting from the combustion of the highly reactive Al particles) (Gonçalves de Miranda, 2000), 120 Tn of CO and CO 2 and 90 Tn of HCl (De Lacour, 2011).…”
Section: Introductionmentioning
confidence: 99%